ADVANTAGES OF DISTANCE LEARNING (World Bulletin of Management and Law, 2022)
This article discusses the advantages, conveniences of distance learning, distance or regular classroom education, saving time and increasing the financial interest of distance education teachers, depending on the level of opportunity.